Open source intelligence gathering and analysis of correlation of cyber risks - Foo, Aloysious Dun Jiat (Nanyang Technological University, 2021)
Cyber attacks are happening every day, with many being oblivious to it and only start to realise the seriousness of it when it happens to them and by the time it will be too late. The impact of cyber threats can be potentially disastrous thus we need to be self educated on them so that we can be better prepared to defend against it with minimal impacts as far as possible. In order to achieve cyber knowledge, proper intelligence needs to be gathered to evaluate the attacks and understand what is going on and to possibly predict what these attacks will do in the future. This project aims to investigate the trends of cyber attacks, such as the types of attacks, who and what they target and their objective. It will be achieved by gathering openly available sources cyber incident data and analysis will be carried out to understand more on the data such as its distributions and their varieties.